Raman threshold and optical gain bandwidth in silica fibers - Felinskyi, G.S.; Korotkov, P.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Nonlinearity of the stimulated Raman scattering (SRS) process in single-mode fibers is the creation basis of the new class of modern photonic devices such as fiber Raman lasers and fiber Raman amplifiers. The quantitative analysis of the gain start conditions and the Raman laser threshold in the single mode fibers from the viewpoint of the strong gain description of active laser materials have been made in this work. It has been shown that the absolute transparency regime for optical transmission in fibers and Raman laser threshold for a monochrome signal wave can be directly obtained from the standard coupled equations using only fundamental fiber parameters. Limiting condition when material of fiber core starts transformation from the natural state with attenuation of the Stokes wave to the state in which the Stokes wave is amplified due to the pumping power may be expressed in a simple analytical form. The numerical data of laser threshold as a function of the wavelength and the examples of gain bandwidth determination for several widespread Raman fibers have been presented.